Searching for evidences for Training in Basic Life Support - a systematic literature review - Tatiane Suely Alves; Ana Luísa P. Cogo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
Training in Basic Life Support (BLS) done by health care providers, such as nurses, is a strategy for the qualification of health care received by the population in general due to the relevance of prompt care to emergency victims. The present exploratory study was a literary review whose objective was to seek evidence of the efficacy of training in BLS for non-health care providers. Eighteen articles were selected from journals published between 2000 and 2005 on the database of the BIREME, according to key words that met the study's objective. Analysis categories were organized according to the topic investigated, types of study, population, sample, methodology, and duration of BLS training. The studies reported herein came predominantly from European countries, were designed for adults (88.9%), and evaluated the retention of knowledge and skills in BLS (50%), using the teaching technique approved by the American Heart Association (39.1%). Of these, two (11.1%) were retrospective studies; the others (88.9%) evaluated ongoing trainings. Trainings designed for laypeople aged 14 and up and given in theoretical-practical lessons divided in different modules showed effectiveness. Retention of skills was found in trainings repeated every six months. The inclusion of the hearing impaired in the performance of BLS was also demonstrated as possible. Further studies designed to develop BLS trainings in Brazil should be conducted in similar and significant samples and populations.